Embedding STEM Learning with Islamic Values and Character Education in the Storybook - Masud, Sulthon; Abdillah, Husni; Munfaati, Kusnul; Erfansyah, Nasrul Fuad; Metafisika, Kartika (International Journal of STEM Education for Sustainability, 2023)
This article aimed to describe a combination between Science, Technology, Engineering, and Mathematics (STEM) learning with religious character while respecting diversity in the story book. This research is part of the research method of designing and developing picture storybooks at the ADDIE model's analysis, design, and development stages. Prototype Design STEM Activity Storybook shows how the picture of project-based learning is implemented. In this storytelling, students can learn how to interact with different tribes, nations, races, and religions to solve environmental problems. In the storybook, there are trigger questions Higher Order Thinking Skills (HOTS) to be discussed in discussions and STEM-Engineering Design Process (EDP). The purpose of developing this book is to illustrate how to combine STEM learning and character education in story books.